Досвід діагностики та лікування первинного гіперпаратиреозу - Павловський, М. П.; Бойко, Н. І.; Хом’як, В. В. (Clinical Endocrinology and Endocrine Surgery, 2009)
In research work authors analysed 78 cases of primary hyperparathyroidism operated in the clinic of faculty surgery department of Lviv national medical university by Danylo Galytski during 1985-2008. Proposed system of "partial" screening improved the diagnostics of primary hyperparathyroidism. In the article efficiency of localization procedures for pathological parathyroid glands was researched; authors showed the results of surgical treatment.